Analisis Indeks Kepuasan Masyarakat terhadap Pelayanan Publik di Puskesmas Kecamatan Pasar Rebo - Elwindra Elwindra; Edi Junaidi (STIKes Persada Husada Indonesia, 2015)
Puskesmas Pasar Rebo Vision is to realize good quality health services for independent healthy society.However, some issues highlighted in public service quality indicates that there are still weaknesse andirregularities which would affect the public's satisfaction. This research is very important to determine thequality of service rendered by the health center as the center of healthcare service delivery. This study willanalyze the quality of services provided by Puskesmas Pasar Rebo. This research is quantitative research withcross sectional approach, with a sample of 150 respondents. As a control, also conducted indepth interviews to the staff. Suitability Level will calculate the level of conformity between the interests and performance.Satisfaction level calculated with Community Satisfaction Index (IKM) with 14 indicators set by the government based on Kep/25/M.PAN/2/2004. Furthermore, Importance-PerformanceAnalysis with Cartesian diagram will clarify the position of each indicator. This study found that the overall index value in Puskesmas Pasar Rebo index score is 2.95, converted to the value of IKM become: 73.70 are included in interval between 62.51 to 81.25. It shows that the quality is B, mean performance PasarRebo Health Center is Good. Suitability Level is equal to 77.76%, which can be concluded that the health center has been providing services that meet the patients expectations. It is recommended to Puskesmas Pasar Rebo to prioritize the elements of service: The precise execution of time schedule, officers discipline, and clarity and certainty of officer.